The Relationship Of Self Esteem And Self Efficacy With Burnout In Elementary School Teachers During The Covid-19 Pandemic - Irmayani Irmayani; Rosita Ginting; Sri Melda Bangun; Raisha Octavariny; Anggi Isnani Parinduri; Riris Hotnauli Manurung (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Burnout is a prolonged work fatigue syndrome characterized by physical, mental and emotional exhaustion caused by the many responsibilities of a job that must be done in a certain period of time. Burnout with Self Esteem and Self Efficacy has a very significant role where the higher Self Esteem and Self Efficacy will result in a lower risk of experiencing Burnout. Explaining the relationship between Self Esteem and Self Efficacy with Burnout to Teachers at RK 4 Private Elementary School and Public Elementary School UPTD No. 122371 Pematangsiantar City during the Covid 19 Pandemic is the purpose of this research. The method used is quantitative associative with a cross-sectional design. All teachers from RK 4 Private Elementary School and UPTD Public Elementary School No. 122371 Pematangsiantar City was used as the population in the study and the sample was drawn by purposive sampling technique and the sample in this study was 30 people. Research data were collected by giving questionnaires to research respondents. The chi square test is used to process the research data. Found a relationship between Burnout and Self Esteem (p = 0.029 < = 0.05) and found a relationship between Burnout and Self Efficacy (p = 0.002 < = 0.05) in this study. Teachers should re-evaluate career goals and determine priorities, take time off to rest, improve Self Esteem and Self Efficacy, and share complaints experienced with those closest to them, even if necessary can do counseling with experts such as psychologists.